Maya Potters' Indigenous Knowledge : Cognition, Engagement, and Practice - Arnold, Dean E., 1942- (Book collections on Project MUSE., 2017)
"Based on fieldwork and reflection over a period of fifty years, Arnold utilizes engagement theory to describe the indigenous knowledge of traditional Maya potters in Ticul, Yucatán, Mexico. Arnold examines craftspeople's knowledge and skills, their engagement with natural and social environments, the raw materials, and their process"--Provided by publisher.